EFFECT OF SPRAY FERTlLlZA TlON OF PHOPHORUS IN, GRAM - Singh, U B; Tomar, S P; Jain, M K (Annals of Arid Zone, 2016)
Gram crop can utilize phosphorus as spray through leaf absorption and can meet its requirements. Utilization efficiency of phosphate application can be increased from 25 to 50% when applied as spray as compared to application of phosphate through band application. A saving in cost of fertilizer can be effected by change of method of application from band to foliar by 2S to 50%. With use of spray phosphate application, area under rabi crop can be increased. by sparing man and bullock power .from fertilizer placement.